2002
DOI: 10.1590/s0074-02762002000200002
|View full text |Cite
|
Sign up to set email alerts
|

Biting Indices, Host-seeking Activity and Natural Infection Rates of Anopheline Species in Boa Vista, Roraima, Brazil from 1996 to 1998

Abstract: The epidemiology of the transmission of malaria parasites varies ecologically. To observe some entomological aspects of the malaria transmission in an urban environment, a longitudinal survey of anopheline fauna was performed in Boa Vista, Roraima, Brazil. A total of 7,263 anophelines was collected in human bait at 13 de Setembro and Caranã districts: Anopheles albitarsis sensu lato (82.8%), An. darlingi (10.3%), An. braziliensis (5.5%), An. peryassui (0.9%) and An. nuneztovari (0.5%). Nightly 12 h collections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
90
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 14 publications
11
90
0
10
Order By: Relevance
“…Moreover, those studies were conducted mostly in the Brazilian Amazon and French Guyana; Soares Gil et al (2003) reported an EIR of 10 infective bites/person/year for An. darlingi in RO, while in urban areas of Boa Vista, Silva-Vasconcelos et al (2002) reported that the highest EIR was in An. albitarsis s.l.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, those studies were conducted mostly in the Brazilian Amazon and French Guyana; Soares Gil et al (2003) reported an EIR of 10 infective bites/person/year for An. darlingi in RO, while in urban areas of Boa Vista, Silva-Vasconcelos et al (2002) reported that the highest EIR was in An. albitarsis s.l.…”
Section: Discussionmentioning
confidence: 94%
“…Study sites -For continuity with and an extension of the study by Silva-Vasconcelos et al (2002) we collected in two localities, 13 de Setembro (along the Rio Branco) and Caranã (along the Rio Cauamé). We chose four additional localities (Cauamé, Jardim da Copaiba, Caçari, and Distrito Industrial) where malaria cases had recently (2000)(2001) been reported to the Secretaria Municipal de Saúde in Boa Vista.…”
Section: Methodsmentioning
confidence: 99%
“…marajoara appears to be the primary malaria vector in Serra do Navio, state of Amapá (Póvoa et al 2000b well as in Boa Vista, state of Roraima (Silva-Vasconcelos et al 2002). An.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Great differences in biting activity patterns have been reported throughout the An. darlingi geographic distribution, from very pronounced crepuscular to almost exclusively nocturnal activity (Forattini 1987, Lourenco-de-Oliveira et al 1989, da Silva-Vasconcelos et al 2002, Moreno et al 2007). In the coastal areas of French Guiana, Pajot et al (1977) showed that An.…”
Section: Parous Rates and Vci -mentioning
confidence: 99%